Circulating Tumor Cells: A Promising Biomarker in the Management of Nasopharyngeal Carcinoma - Wu, Jiangtao; Zhu, Huijun; Gao, Feifei; Wang, Rensheng; Hu, Kai (Frontiers in Oncology, 2021)
Nasopharyngeal carcinoma (NPC) is a malignancy that arises from the mucosal epithelium of the nasopharynx, and its prognosis is relatively favorable. The 5-year overall survival rate in patients with locally advanced NPC currently exceeds 80%, but the development of individualized diagnosis and treatment at the molecular level is relatively lacking. Circulating tumor cells (CTCs) is the generic term for tumor cells that are present in the peripheral blood circulation. As a new biomarker with good clinical application prospects, the detection of CTCs has the advantages of being non-invasive, simple, and repeatable. By capturing and detecting CTCs in peripheral blood and monitoring the dynamic variation of its type and quantity, we can assess the biological characteristics of tumor in a timely manner and evaluate the therapeutic effect and prognosis of patients in advance, which will help to develop individualized treatments of tumors. The primary purposes of this review were the clinical application of CTCs in tumor stage determination, treatment efficacy evaluation, and prognosis prediction of NPC. In addition, we estimated the correlation between Epstein-Barr virus infection and CTCs and analyzed the difference in karyotypes and specific markers expressed on CTCs. We believe that our study will provide new insights and biomarkers for the individualized treatment of patients with NPC.